Tapered Plastic Optical Fiber Coated With HEC/PVDF for Measurement of Relative Humidity - Batumalay, Malathy; Lokman, A.; Ahmad, F.; Arof, Hamzah; Ahmad, Harith; Harun, Sulaiman Wadi (Institute of Electrical and Electronics Engineers (IEEE), 2013)
A simple humidity sensor is proposed and demonstrated using a tapered plastic optical fiber (POF) as a probe. Its operation is based on intensity modulation technique using a tapered POF probe coated with a polymer blend of hydroxyethylcellulose/polyvinylidenefluoride (HEC/PVDF) composite that acts as the humidity sensitive cladding. The sensor is fabricated using an etching method and has a waist diameter of 0.45 mm and tapering length of 10 mm. As the relative humidity varies from 50% to 85%, the output voltage of the sensor increases linearly from 0.32 to 1.25 mV. The HEC/PVDF composite-coated sensor exhibits a sensitivity of 0.023 mV/% with a slope linearity of . The sensitivity of HEC/PVDF composite-coated cladding toward humidity stems from its ability to swell as humidity increases in the atmosphere resulting in a drop in its refractive index below that of the core and thus allowing more light to be transmitted through the tapered fiber.